2016
DOI: 10.1002/admi.201600014
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Alumina Barrier Coatings on Glass: MOCVD Process and Hydrothermal Aging

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 15772 [ 9 ] radio frequency magnetron sputtering, [ 2 ] atomic layer deposition, [ 10 ] sol-gel, [ 5 ] and metalorganic chemical vapor deposition (MOCVD). [ 7,[11][12][13] CVD is one of the most attractive techniques for the time effi cient deposition of such coatings on com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…17 In contrast, the films obtained from DLI ATI show a columnar growth of agglomerated nodules. 20 This microstructure contrasts strikingly with the one observed for films grown using evaporated ATI suggesting that the solvent (cyclohexane) used in DLI plays an important role in the nucleation and growth of the film. Secondly, EPMA and XPS analyses showed that the O/Al ratio is generally different from the one of stoichiometric alumina (O/Al = 1.5) over a wide range of temperature.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…17 In contrast, the films obtained from DLI ATI show a columnar growth of agglomerated nodules. 20 This microstructure contrasts strikingly with the one observed for films grown using evaporated ATI suggesting that the solvent (cyclohexane) used in DLI plays an important role in the nucleation and growth of the film. Secondly, EPMA and XPS analyses showed that the O/Al ratio is generally different from the one of stoichiometric alumina (O/Al = 1.5) over a wide range of temperature.…”
Section: Introductionmentioning
confidence: 78%
“…Deposition experiments were performed in a custom-made, horizontal, hot-wall CVD reactor described in previous works. [17][18][19][20] Films were grown on either 50 mm (University wafer) or 100 mm thick (Sil'tronix), (100) oriented silicon wafers. Using thinner Si substrates increases the amount of alumina material in the NMR probe, which reduces the measurement time and/or increases the signal to noise ratio.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the limitation of the low precursor volatility, a more efficient delivery system like Direct Liquid Injection (DLI) could be used [49], in order to work with much higher inlet precursor molar fractions. Thanks to its versatility, the FBCVD process allows depositing various metals or metalloids on MWCNTs or on other porous or nonporous powders, this opening the way for the industrial production of innovative multi-functional materials in the fields of catalysis, Li-ion battery, and composite materials.…”
Section: Resultsmentioning
confidence: 99%